Larger Foraminifera from Eniwetok Atoll drill holes - Cole, W. Storrs (William Storrs), 1902-1989 (Bikini and nearby atolls, Marshall Islands., 1957)
"Sixty-two species and one variety of larger Foraminifera from Eniwetok Atoll drill holes are identified; 11 are new."